Detection and molecular characterization of mycoplasma gallisepticum and mycoplasma synoviae from commercial chickens in Malaysia - Ahmad, Kartini (2012)
Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) are wellknown pathogens of poultry, which are distributed world-wide and significantly important for the poultry industry. Both pathogens are capable causing respiratory and joint diseases in chickens and turkeys, subsequently leading to poor production due to poor growth and increase in mortality. Currently, studies on the prevalence of MG and MS, especially on concurrent infections with MG and MS, in commercial chickens as well as genetic diversity of MG and MS isolates are still lacking in Malaysia. Hence, the present study was to detect the presence of MG and MS from commercial chickens (broiler, breeder, layer and village chickens) in Peninsular Malaysia using isolation and molecular methods; and to characterized multigene families of MG (pvpA, gapA, mgc2, pMGA, crmA3 and crmC genes) and MS (vlhA gene) based on gene-targeted sequencing (GTS) analysis. A total of 814 samples of choanal slit and trachea swabs from 27 chicken farms within Peninsular Malaysia were taken from 472 commercial broiler, 105 broiler breeder, 131 layer and 106 village chickens. Mycoplasma gallisepticum was detected in three out of four types of commercial chickens farms (broiler, broiler breeder and village chickens), while MS were detected in all four commercial chickens farms (broiler, broiler breeder, layer and village chickens). Overall, both IFA and PCR methods detected high prevalence of MG infection (9.1% and 24.2%, respectively) than MS infection (2.0% and 5.7%, respectively), while concurrent infection of MG and MS (0.7% and 2.5%, respectively) was the least detected in this study. The prevalence of MG infection and concurrent MG and MS infections were detected higher in broiler chickens followed by broiler breeder, layer and village chickens. Mycoplasma synoviae was detected higher in broiler breeder chickens followed by broiler, layer and village chickens. These indices indicate that MG and MS are still persisting in commercial poultry production under current biosecurity and disease control programme. The analysis of multigene families of 20 MG field isolates on six cytadhesin genes revealed their G+C content within 27% - 50% and showed 91-100% sequence homology with MG isolates from USA, Israel, Australia and Russia. Classification of field MG isolates based on a close relationship on nucleotide sequence analysis,sequence similarity identity matrix and phylogeny relations, revealed eleven (11) Malaysian MG field isolates were successfully grouped into 3 categories: 1) S6 strain, 2) ts-11 strain and 3) local field strain. Five isolates (KPR44 L,KPR16W44 L, THNG8W L, PF3H Br and PF7U Br), under local field strain category, were classified as Malaysian isolate as they were more diversified than the reference and published isolates. Analysis on eight MS local isolatesbased on size of proline-rich repeat (PRR) region of the vlhA gene revealed gene size polymorphism with 41 - 43% G+C content and 95 - 98% sequence homology with Australian and USA isolates. The lengths of PRR encoding sequence of local isolates were within 19 - 35 amino acids and the isolates were classified according to PRR grouping (group A - E). Two field isolates (ALNH5 BB and LHMN L) were classified in group C with 32 a.a. and one isolate (JBSJ Br) was classified in group E with 19 a.a. However, five local isolates (KSVC4 VC, KSVC5 VC, LGW34H9 BB, PPB07 Br and ALNH6 BB) with 35 amino acid (a.a.) size were not classified within the PRR classification as there is no classification on 35 a.a. been published or recorded. These new findings show the unique entity of Malaysian MG and MS field isolates compared to reference and other published isolates.